PRÁTICAS DE MODELAGEM MATEMÁTICA NO ÂMBITO DO ENSINO FUNDAMENTAL: UM OLHAR A PARTIR DE RELATOS DE EXPERIÊNCIA - Kaviatkovski, Marinês Avila de Chaves (2017)
This work presents an analysis of how Mathematical Modeling is being inserted in the school context, in the field of an investigation that seeks to answer what the Reports of Experience point to regarding the practices of Mathematical Modeling, within the scope of Elementary Education. The research design is predominantly qualitative / interpretative. The data was obtained through documentary research. The treatment of the data occurred according to the meta-analysis in Larocca, Rosso and Souza (2005). The objective of the research is to point out, after analytical reflections on the experience reports, what is shown in the Mathematical Modeling practices presented in the events of Mathematics Education, within the scope of Elementary Education. We analyzed 76 reports of experience presented and included in the annals of the main specific events of Mathematical Modeling and Mathematical Education, in which Mathematical Modeling is thematized, in the editions realized in-between 2005 to 2014. We utilized as theoretical grounds the contributions of authors: which discusses the nature and methodology of Mathematical Education (Rius, 1989a, 1989b), author who bases the aspects and analysis of the data of a qualitative research (Bardin, 2011), as well as authors that discuss the practices of Mathematical Modeling (D’Ambrosio, 1999; Burak, 1992, 2010; Burak; Klüber, 2008, 2010), as well as authors who discuss the Education (Freire, 1981, 2002, 2005, Vygotsky,1984). The results of the research indicate that the Modeling practices, within the scope of Elementary Education: i) provides a learning with meaning and sense to the students; ii) contemplate all fields of Mathematics; iii) value students' knowledge; iv) promote dialogue and interaction among students; v) modify the way students perceive Mathematics, among other aspects.